“Genuine anecdotes about Peter the Great” by J. Shtelin, Translated by A. A. Nartov — an Unknown Monument of Russian Literature of 18th Century - P. A. Krotov (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
The problem of the development of a small literary genre of historical anecdote in Russia in the second half of the 18th century is researched. The question is raised on the manuscript of the translation of “Genuine anecdotes about Peter the Great” by Academician J. Shtelin (1709—1785) into Russian, which was made by the famous person of the Age of Enlightenment A. A. Nartov (1736/1737—1813) in 1785. The relevance of the study is due to the fact that the article is the first study of the manuscript, which remained unpublished and was not the subject of research. It is proved that Nartov’s translation of Shtelin’s work became an impetus for him to create his own historical and literary work, now known as Nartov’s Tales of Peter the Great (1786). It is concluded that Nartov’s collection of historical anecdotes is a literary work, which was created with extensive use of Shtelin’s “Genuine anecdotes about Peter the Great”. The study of Nartov’s manuscript also made it possible to establish that the author of the first translation of Shtelin’s work published in Russia (1785) was the famous translator and publisher P. I. Bogdanovich.